The Application of Neo-Vernacular Architecture in the Redesign of the Aceh Arts and Culture Park in Banda Aceh - Wulandari, Utami; Idawati, Dyah Erti; Nursaniah, Cut (Universitas Syiah Kuala, 2025)
Acehs diverse cultural heritage expressed through music, dance, theater, and traditional customs, highlights the need for a dedicated space to preserve and promote local arts. This study aims to redesign the Aceh Arts and Culture Park in Banda Aceh using Neo-Vernacular Architecture, an approach that combines traditional values with modern design principles. The design adopts five key principles: Direct Connection, Abstract Relationship, Landscape Integration, Contemporary Interpretation, and Future Relationship. These are reflected in the form, massing, and faade treatments inspired by elements of Acehnese culture such as the Rumoh Aceh, traditional dances, and local customs. Located on Teuku Umar Street with a site area of approximately 31,000 m, the park is designed as a cultural hub equipped with supportive facilities. Using a qualitative method, the research involves field surveys and literature review. The study finds that the Neo-Vernacular approach reinforces cultural identity, improves climate responsiveness, and enhances the parks function as a center for cultural preservation and tourism. The project is expected to establish a new architectural identity for Banda Aceh and attract both local and international visitors.